MAKNA PERJUANGAN DALAM NOVEL INDONESIA BERLATAR PERANG KEMERDEKAAN (TINJAUAN NEW HISTORICISM GREENBLATT) - Wicaksono, Andri (Jurnal Pendidikan Bahasa dan Sastra, 2018)
Through this new approach of historicism, this study aims to reveal the construction of the meaning of "striving" in a new historical perspective, either by 'republican' or ruler (colonist who wants to set foot again). The novels characterized by the background during the independence war were chosen to be the primary data source in this study. The method used in the research is qualitative interpretive, namely the parallel reading between literary texts representing the history of the Indonesian struggle with historical texts depicting similar events. Data analysis techniques used are content analysis consisting of three paths, including: data reduction, data presentation, and conclusion drawing or verification. The results showed that the meaning of the struggle in the novel consists of two points of view, namely for the republic and ruler (colonizers: England who dibonceng NICA). From the perspective of freedom fighters, the republic considers the figures involved to show respect for the national struggle and to contribute to defending the independence already achieved. As for the opposite, for the colonizing nation (the Netherlands), struggling in that perspective is no more proper "terrorist and thief".